Fundamentals of signals and systems using MATLAB - Kamen, Edward W (Prentice Hall, 1997)
For a one-quarter or one-semster course on Signals and Systems. This new edition delivers an accessible yet comprehensive analytical introduction to continuous-time and discrete-time signals and systems. It also incorporates a strong emphasis on solving problems and exploring concepts, using demos, downloaded data, and MATLAB(r) to demonstrate solutions for a wide range of problems in engineering and other fields such as financial data analysis. Its flexible structure adapts easily for courses taught by semester or by quarter.